Sehat Berinternet untuk Anak Sekolah Selama Masa Pandemi di SD IT Ulul Albab - Ria Rismayati; Ismarmiaty Ismarmiaty (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The impact of the Covid 19 pandemi, which began in 2020, has changed almost all aspects of life, especially teaching and learning activities. Teaching and learning activities which are generally carried out face-to-face, during this pandemi, were implemented online or online using the internet media. The use of the internet among ustadz, ustadzah and students of SD IT Ulul Albab is not an obstacle, especially as children in this era grow up with the internet which has become an important part of the surrounding environment and the internet is easily accessed at home, school and other public facilities. From every facility obtained from the internet, of course, it produces 2 sides that are positive and negatif, and to reduce the negatif impact of activities that involve the internet, there is a need for assistance, direction and socialization of the internet in a healthy and safe manner. In the service that was carried out at SD IT Ulul Alabini, it was given assistance and socialization to ustadz and ustadzah in representing healthy internet access which would then be passed on to their students. From this service, an evaluation was also carried out by distributing questionnaires related to the results of the socialization carried out in conveying the material, that the participants of this service gained added value to utilize the internet media in a healthy manner as a learning tool for 89% of the participants who attended.